Abnormalities of skeletal muscle metabolism in patients with chronic heart failure: evidence that they are present at rest. Issue 2 (February 1997) - Andrews, R.; Walsh, J. T.; Evans, A.; Curtis, S.; Cowley, A. J.
Abstract : OBJECTIVE: To investigate abnormalities of skeletal muscle metabolism in patients with congestive heart failure. SETTING: A university teaching hospital. METHODS: 43 patients (22 New York Heart Association (NYHA) grade II, 21 grade III) and 10 controls were studied. A forearm model of muscle metabolism was used, with a cannula inserted retrogradely into an antecubital vein of the dominant forearm. Maximum voluntary contraction (MVC) was measured using handgrip dynamometry. Subjects performed handgrip exercise, 5 s contraction followed by 5 s rest for 5 min at 25%, 50%, and 75% of MVC or until exhaustion. Blood was taken at rest and 0 and 2 min after exercise for measurement of lactate and ammonia. After 30 min the procedure was repeated with fixed workloads of 7 kg, 14 kg, and 21 kg. RESULTS: MVC (kg, mean (SEM)) was lower in patients than in controls (control 42.45 (2.3); NYHA II 34.13 (1.3), P = 0.003; NYHA III 33.13 (1.94), P = 0.008). Resting lactate (mmol/l) was higher in patients than controls (control 0.65 (0.06); NYHA II 0.84 (0.08), P = 0.13; NYHA III 1.18 (0.1), P = 0.002). Resting ammonia (mumol/l) was higher in NYHA III (65.7 (6.0)) than in NYHA II (48.0 (3.7), P = 0.016); no difference was found between controls (48.0 (7.1)) and patients. The overall lactate and ammonia response to exercise was greater in NYHA III than in NYHA II and controls (P < 0.05). At volitional exhaustion, peak lactate (mmol/l: NYHA III 3.31 (0.26); NYHA II 2.56 (0.16); controls 2.71 (0.22); P = 0.022 NYHA III v NYHA II) and ammonia (mumol/l: NYHA III) 126.4 (8.97); NYHA II 92.9 (7.23); controls 109 (16.3); P = 0.006 NYHA III v NYHA II) were higher in severe congestive heart failure. CONCLUSIONS: Skeletal muscle metabolism is abnormal at rest in congestive heart failure. During exercise, the degree of metabolic abnormality is related to the symptomatic status of the patient.